IDENTIFIKASI SENYAWA GOLONGAN FENOL DARI EKSTRAK ETANOL DAUN SIRIH HIJAU (PIPER BETLE LINN.) DENGAN METODE KLT-SPEKTROFOTODENSITOMETRI - Susanti, Ni Made Pitri; Dewi, Luh Putu Mirah Kusuma; Manurung, Harlina Setiawati; Wirasuta, I Made Agus Gelgel (Metamorfosa: Journal of Biological Sciences, 2017)
Phenol compound in Piper betle leaves has several pharmacology activities such as antibacteria, antifungi and antioxidant. The pharmacology activities of a herbal drug are influenced by the phytochemistry content, so in order to do a quality determination that provides phytochemistry profile and consistent pharmacology activities, a standardization is required. Fingerprint is the main standard to perform quality control for herbal drug. TLC-spectrophotodensitometry was used as the method in order to provide fingerprint profile of phenol compound. In this experiment, Piper betle leaves samples were extracted by reflux method using ethanol 96% as the solvent. Identification of phenol compound was done using TLC-spectrophotodensitometry with Silica gel 60 F254 as the stationary phase, toluena: ethyl acetate (93:7 v/v) as the mobile phase, FeCl 3 and Folin-Ciocalteau as the reagent. The fingerprint profile of phenol compund was shown in Rf value 0,19; 0,42; and 0,62. Positive results of phenol compound are black spot on FeCl 3 colour test and dark blue spot  on Folin-Ciocalteau colour test. Maximum wavelength of phenol compound was 283 nm.
Keywords: Piper betle, phenol, fingerprint, TLC-spectrophotodensitometry